Evaluation of field epidemiology training programs: a scoping review - Al Nsour, Mohannad; Khasawneh, Ghena; Khader, Yousef; Bashier, Haitham (Frontiers in Epidemiology, 2024)
Objectives Field Epidemiology Training Programs (FETPs) are competency-based training programs that play a critical role in strengthening global health security and enhancing the epidemiological capabilities of public health professionals. This scoping review examined available published literature on the evaluations of FETPs globally. Methods A literature review was conducted to evaluate FETPs globally. Keywords specific to the evaluation of FETPs were utilized to search the PubMed, Scopus, and Web Science databases. After applying the inclusion and exclusion criteria, 12 relevant studies from an initial pool of 60 were included in this study. Data extraction included key details, and a qualitative synthesis organized diverse findings using a narrative approach to draw appropriate conclusions and generate recommendations. Results The review covered findings from 12 studies covering all three FETP modalities and spanning countries in various regions. Evaluations explored gained skills, engagement in FETP activities, and improvements in field epidemiological functions. Gained skills and knowledge, engagement in FETP activities, and improvements in field epidemiological functions were evident, with specific expectations for each FETP tier. Positive outcomes were consistent across studies, revealing improvements in surveillance activities, outbreak response, data management, and other system functions. Conclusion This review confirmed the positive impact of FETPs on trainees and graduates, which emphasized competency enhancements across different modalities. Various strategies are recommended to improve the evaluation of FETPs. For effective evaluation, it is necessary to develop robust evaluation tools and establish standardized metrics to compare FETPs across regions or countries.